Evaluasi Implementasi Kurikulum 2013 pada Pembelajaran di Sekolah Dasar - Hikmah, Nur (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
This research focuses on the evaluation of the implementation of the 2013 Curriculum in MI Ma'arif NU Batuanten, Cilongok, as part of efforts to improve the quality of primary education in Indonesia. The 2013 Curriculum is expected to produce graduates who not only have academic competence but also creativity, innovation, and character in line with the demands of the era.The research results indicate that the implementation of the 2013 Curriculum brings significant changes in the approach to learning. Teachers perceive a shift towards a more student-centered approach, emphasizing understanding of concepts, and encouraging the application of knowledge in daily life. However, the main challenges related to resource availability and adequate understanding of the new curriculum persist. Strategic recommendations proposed include enhancing teacher training and development, increasing resources, and encouraging more active parental involvement in supporting children's education. Ongoing evaluation and improvement must be an integral part of the education system to ensure that the 2013 Curriculum provides maximum benefits for the quality of primary education. The implications of this research suggest that to enhance the effectiveness of the implementation of the 2013 Curriculum, involvement of all relevant stakeholders, effective coordination, and commitment to building education in line with the needs of the times are essential. A profound understanding of educational theories such as constructivism and collaborative learning can guide further improvements in implementing this curriculum. By focusing on appropriate improvements and changes, it is expected that the implementation of the 2013 Curriculum can achieve the desired goals: producing future generations that are intelligent, creative, innovative, and have strong characters. These improvement measures are an investment in the future of Indonesian education, which will have a positive impact on global competition.